Optimalisasi Akuntansi Syariah dalam Meningkatkan Transparansi Pengungkapan Laporan Keuangan pada Lembaga Keuangan Syariah - Nuranjani Nuranjani; Efa Fadillah; Tri Aryana; Masyhuri Masyhuri (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study examines how optimizing Islamic accounting strengthens the transparency of financial disclosures in Islamic financial institutions through a structured review of authoritative literature, including AAOIFI standards, PSAK Syariah, and contemporary academic works on Islamic finance. Findings show that Islamic accounting provides a value-based reporting foundation integrating ethical, social, and spiritual dimensions that conventional accounting does not fully capture. Strengthening Islamic accounting standards enhances the clarity of transaction recording, reduces interpretation bias, and improves disclosure quality, especially for contracts such as murabahah, mudharabah, musyarakah, and ijarah. The integration of Islamic accounting information systems further increases transparency by ensuring real-time data processing, improving reconciliation accuracy, and enabling deeper disclosures for zakat and other social funds. Literature consistently emphasizes that institutions with strong adherence to Islamic accounting standards demonstrate higher levels of accountability, stakeholder trust, and compliance with syariah principles. Overall, the study concludes that optimizing Islamic accounting is essential for improving financial disclosure transparency and supporting sustainable governance in Islamic financial institutions.